Entrepreneurial Intention: The Mediating Role Of Entrepreneurial Mindset And Entrepreneurship Education - Regita Putri Utami; Fatmah Bagis; Hengky Widhiandono; Alfato Yusnar Kharismasyah (Cita konsultindo, 2025)
This study aims to examine the relationship between entrepreneurship education, entrepreneurial culture and entrepreneurial intention and investigate the mediating role of entrepreneurial mindset and entrepreneurship education in the relationship between entrepreneurship education and entrepreneurial intention. This study was conducted on 327 active students of the faculty of economics and business at the 3 largest universities in Purwokerto, Indonesia. Sampling was conducted using stratified random sampling technique that fulfils the required criteria, and questionnaires were distributed directly. Data analysis using SEM-PLS with Smart Partial Least Squares (SmartPLS) software. This study shows that an entrepreneurial mindset has successfully accelerated students' entrepreneurial intentions. Partially, entrepreneurial culture has an impact on entrepreneurship education and entrepreneurial intention. In addition, entrepreneurship education and entrepreneurship culture have a strong correlation with students' entrepreneurial mindset. Contrary to expectations, this study found no significant difference between entrepreneurship education and students' entrepreneurial intention. This result implies that the university has positioned itself as an important intervention in encouraging students' intentions through an effective entrepreneurship education model.